B .R. Ambedkar - "Janak, Singh" (Delhi, 2010)
Even though Bhimrao Ramji Ambedkar was the most outstanding Indian among all his contemporaries, justice was never done to him at least in India, though he had many admirers abroad. Just when he was trying to settle down as law minister in free India's first Cabinet and was grabbing headlines by his brilliant speeches in Parliament, he was eased out. Caste leaders could never reconcile themselves to the fact that an Untouchable Mahar Ambedkar was could be so brilliant as to have better of them in debate or repartee. Thanks to the machinations of the caste lobby, he could never get elected to the Lok Sabha despite the fact that lakhs of untouchables all over the country had come to regard him as their messiah. Because of his revolutionary ideas to overturn the caste system, Gandhi said: "He was the greatest challenge to Hinduism." What went into the making of Ambedkar and how in his lifetime he went on conquering peaks of excellence despite hurdles, roadblocks, apathy of the caste leaders is the story of this book the reading of which can make one's flesh creep even today. About The Author:- Janak Singh, a former Deputy Bureau Chief of the Times of India, is a widely traveled journalist, who has been writing for over three decades. He has extensively reported on crime, social problems, academic issues and political parties.
Keywords: "Ambedkar, B R"